A predictive model of loss time due to low back pain among garment sewers in Bulacan - Lugay, Carlos Ignacio P. (1999)
Filipinos have been used to seeing small tailoring and ladies garment shops in almost every corner of the street. And in almost all households, there is usually a manually-operated sewing machine in one corner of the house. In fact, to emphasize how skilled the Filipinos are in garments assembly, garments export has been the country's number tow export since the early 80's.
In this line, quite a number of enterprising Filipinos have put up small-sized garment companies as means of livelihood. However, given the increasing competition from neighboring countries, such as China and Vietnam, which has been offering cheaper labor rates, an obvious pattern of dwindling garment exports is being seen.
Thus, the government has been looking for means of increasing productivity of the said sector. As a contribution to this effort, this study will help owners/production supervisors determine the loss of time garment sewers due to low back pain (LBP). through equation models this study will be able to approximate the number of minutes a sewer will render to recover from LBP. This will be a substantial assistance to the production planners since they will be able to approximate the possible output per day and hence do any remedial measures if needed be.
Thesis (M.S. Industrial Engineering)--University of the Philippines, Diliman.
Keywords: Clothing workers -- Philippines -- Bulacan; Clothing trade -- Employees -- Diseases -- Philippines -- Bulacan; Clothing trade -- Labor productivity -- Philippines